20.5k views
3 votes
Can you help me answer 6, 9 and 12 please

Can you help me answer 6, 9 and 12 please-example-1

1 Answer

4 votes

f(z)=(3z^2)/(5z^2+7z)

First, we can factorize z from the denominator, then we can cancel one z


(3z^2)/(5z^2+7z)=\frac{3z^2}{(5z^{}+7)z}=\frac{3z}{5z^{}+7}
f(z)=\frac{3z}{5z^{}+7}

Then applying the quotient rule


f^(\prime)(z)=((g\mleft(z\mright))/(h(z)))^(\prime)=(h(z)g^(\prime)(z)-h^(\prime)(z)g(z))/(h^2(z))
\begin{gathered} g(z)=3z \\ g^(\prime)(z)=3 \end{gathered}
\begin{gathered} h(z)=5z+7 \\ h^(\prime)(z)=5 \end{gathered}


f^(\prime)(z)=(\frac{3z}{5z^{}+7})^(\prime)=((5z+7)\cdot3-5(3z))/((5z+7)^2)
f^(\prime)(z)=(15z+21-15z)/((5z+7)^2)=(21)/((5z+7)^2)

the derivate is


(21)/((5z+7)^2)

User Disapamok
by
5.6k points